Boj med Ilirijo in Primorjem za prevlado v slovenskem nogometu in nastanek reprezentančnega ljubljanskega nogometnega moštva z imenom SK Ljubljana - Mudražija, Tin (Studia Historica Slovenica, 2018)
The article deals with the football rivalry between the biggest, most successful and most dominant Slovenian football club of the first half of the 20th century named SK Ilirija (Sportni klub Ilirija) and its main rival, the main football club of the people from the Primorska region living in Ljubljana named AŠK Primorje (Akademski športni klub Primorje). The author points out that the rivalry cost both clubs tremendous moral and material resources; instead of focusing on sports endeavors, they fought for power in the Ljubljana Football Sub-association, trying to score by administrative decisions when unable to win games on the pitch. The main objective of the article is to present the background of the chaotic situation in Slovenian football in the 1920s and 1930s that was the result of struggle between two most successful Slovenian football clubs in the first half of the 20th century. The article also comments on the circumstances that led to the merger of the football teams of SK Ilirija and AŠK Primorje and the foundation of the new, national football team from Ljubljana named SK Ljubljana (Sport klub Ljubljana).
Keywords: 1919-1940; Ljubljana; nogomet; zgodovina